K2 crew performance: a preliminary investigation of kinetic parameters in preferred and inverted positions among sub-elite kayakers - Romagnoli, Cristian; Edriss, Saeid; Caprioli, Lucio; Ghelardini, Luca; Cariati, Ida; Alashram, Anas; Lanotte, Nunzio; Boatto, Paolo; Padua, Elvira; Bonaiuto, Vincenzo; Annino, Giuseppe (Frontiers in Physiology, 2024)
K2 performance depends on different kinematic and kinetic variables. Due to the lack of related studies in this area, we have tried to explain these features to better understand the best positioning of paddlers and how their synchronization affects performance. This study uses the DAQ system comprising two instrumented paddles—an IMU and a GPS (“E-kayak” system)—to investigate paddle synchronization and the specific positioning of paddlers’ in preferred and inverted configurations. In this study, 10 sub-elite paddlers participated, divided into five crews. The test included two trials of 500 m performed in preferred and inverted seating positions. The synchronization analysis highlighted that the rear paddler contributed efficiently to the propulsion of the boat while performing 30–40 ms earlier than the front paddler during the entry and exit phases. Despite the time results for 500 m, there is no evidence indicating a dominant indication of the preferred or inverted position among the athletes. The results show a significant correlation (p < 0.05) between the force of the front paddler (r = −0.88), the stroke frequency of the crew (r = −0.66), and the total force applied by the crew with the time for 500 m and between stroke frequency and the force of the front paddler (r = 0.64). Based on these indications, for only those crews who completed the 500 m test in the shortest time, the equation determining the time over 500 m was calculated using multiple regression analysis, considering the stroke frequency and the force of the front and rear paddler. The data showed a good estimation with CV% = 0.22, ICC = 0.99, and ES = −0.005. In conclusion, these findings can serve as a beneficial tool for assessing or monitoring K2 crew performance in sub-elite paddlers.